2014
DOI: 10.11648/j.ajam.20140204.14
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pressure Distributions for a Finite Elastohydrodynamic Journal Bearing Lubricated by Ferro Fluids with Couple Stresses

Abstract: The performance of finite elastohydrodynamic journal bearings lubricated by ferrofluids with couple stresses has been studied. We derive a Reynolds equation that takes into account magneto elastohydrodynamics, by using the continuity and momentum equations. The equation has been integrated locally across the film thickness and an equation for the pressure gradient obtained as a function of film thickness and total mass flow rate of lubricant, the modified Reynolds equation. The modified Reynolds equation obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Results showed that the polymer additives in lubricant significantly increased the stability, load carrying capability and decreased the CoF compared to Newtonian lubricants. The magnetic effect in the couple stress lubricants was studied for hydrodynamic [29] and elasto-hydrodynamic [30] journal bearings and improvement in bearing performance characteristics was found. It was observed that the increase in temperature enhanced the magnetism and couple stress parameter.…”
Section: Couple Stress Lubricantsmentioning
confidence: 99%
“…Results showed that the polymer additives in lubricant significantly increased the stability, load carrying capability and decreased the CoF compared to Newtonian lubricants. The magnetic effect in the couple stress lubricants was studied for hydrodynamic [29] and elasto-hydrodynamic [30] journal bearings and improvement in bearing performance characteristics was found. It was observed that the increase in temperature enhanced the magnetism and couple stress parameter.…”
Section: Couple Stress Lubricantsmentioning
confidence: 99%
“…Daniel et al [1] applied a numerical method to analyze the performance of an elastohydrodynamic journal bearing which is lubricated with ferrofluids, using couple stresses. By increasing the couple stresses and magnetism, temperature in the bearing increases.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the effect of Prandtl and Eckert numbers on temperature is investigated in their research. Daniel et al [2] also analyzed magneto-electrohydrodynamics by deriving the Reynolds equation through employing continuum and momentum equations. Pressure distribution in the journal bearing was obtained which indicated an increase in the pressure by enhancement of magnetism and couple stresses.…”
Section: Introductionmentioning
confidence: 99%